Pengeloaan Dana Desa (DD) Dalam pembangunan Fisik di Desa Bumi Etam Kecamatan Kaubun Kabupaten Kutai Timur - Muhammad Hasby Moa Walil Amrih; Letizia Dyastari (Jurnal Ilmu Pemerintahan, 2024)
This research aims to understand and describe the management of Village Funds in physical development in Bumi Etam Village, Kaubun District, covering the stages of planning, implementation, administration, and accountability reporting. Additionally, this research identifies the supporting and inhibiting factors in the management of village funds for physical development in the village. The data collection technique used in this research is Purposive Sampling. The results of the study indicate that the management of village funds for physical development in Bumi Etam Village, Kaubun, has complied with the applicable regulations. The stages of planning, implementation, and administration have been carried out well, with funds being systematically recorded in various financial documents, including SISKUEDES, after going through the coordination and verification processes by the village head and secretary. The inhibiting factors for development in Bumi Etam Village include the uncertainty of natural conditions during project implementation and the limited local human resources. Conversely, the supporting factors include favorable geographical conditions for access to construction tools and materials.In conclusion, the management of Village Funds has complied with the applicable regulations. The stages of planning, implementation, administration, and reporting have been carried out well. However, to enhance transparency, the village government is advised to facilitate community access to village financial reports. The policy for using Village Funds should remain based on existing regulations to prevent misappropriation. Development practices should be in favor of community interests and be sustainable, with full participation from the community and high cooperation.